Reaction kinetics for the production of methylene urea from synthetic human urine. Issue 2 (June 2016) - Kabore, Steve; Ito, Ryusei; Funamizu, Naoyuki
Abstract: The production of methylene urea from human urine is an important contribution to the world demand of nitrogen fertilizer. In this study, a simplified reaction model was proposed. The kinetics parameters at room temperature were assessed and the reaction constants k1, k2, k3, k4 were evaluated and determined for the different parts of the proposed reaction model. The relationship between the Formaldehyde/Urea (F/U ratio) and the recovery of nitrogen was also evaluated based on the contribution of the by-products from the reaction. The optimum F/U condition to maximize the recovery of nitrogen was determined.